Effects of humate, Yucca, and humate-Yucca combination supplementation on growth performance, gut health, and immune response in broiler chickens - Mert, Selim (Frontiers in Veterinary Science, 2025)
This study evaluated the effects of dietary humate (300 mg/kg), Yucca (100 mg/kg), and their combination (300 mg/kg H + 100 mg/kg Y) on growth performance, intestinal microbiota, ileal digestibility, and blood parameters in broiler chickens. A total of 240 one-day-old Ross 308 broiler chicks were randomly divided into four groups and reared for 42 days. Growth performance significantly improved in the supplemented groups. Body weight gain and feed conversion ratio were better in the humate and Yucca groups, with the highest improvement observed in the combination group (HY), which showed a feed conversion ratio close to 1.50 compared to 1.66 in the control. In gut microbiota, E. coli counts decreased notably from over 5.3 log CFU/g in the control to around 2.0 in the HY group. Lactic acid bacteria and total bacterial counts increased by approximately 1.2–2.3 log CFU/g with supplementation. Ileal digestibility also improved: crude fat digestibility increased from 85.8% in the control to 88.1% in HY; crude protein from 85.1 to 87.1%; and organic matter from 83.4 to 85.5%. Blood analysis showed higher immune markers in supplemented groups. IgA levels increased from 9.5 mg/dL to nearly 11.0 mg/dL, and IgM from 7.1 to 8.3 mg/dL. Thyroid hormones T3 and T4 also increased slightly, indicating improved metabolic activity. In conclusion, humate and Yucca especially in combination positively affected gut health, nutrient utilization, immune function, and overall performance in broiler chickens, suggesting their potential as effective natural feed additives.